LGBT REGULATORY VOID: THE URGENCY OF FORMING LOCAL REGULATIONS WITH A HUMAN RIGHTS PERSPECTIVE - YUDI SAPUTRA (Yayasan Pendidikan Aksara Cendikia, 2025)
The phenomenon of Lesbian, Gay, Bisexual, and Transgender (LGBT) remains a contentious socio-legal issue in Indonesia, including in Bima Regency, which has a strong socio-religious character. The absence of specific regulations regarding LGBT issues creates a legal vacuum, resulting in unclear handling and policy implications. This situation results in uncertain norms, weak law enforcement, and an increased risk of social discrimination against LGBT groups. This study aims to analyze the absence of LGBT regulations in Bima Regency and the urgency of establishing Regional Regulations that align with community needs and human rights principles. The method used is normative juridical with statutory, conceptual, and comparative approaches. Primary legal materials include the 1945 Constitution, the Criminal Code, the Human Rights Law, and other regional regulations related to LGBT issues. Secondary legal materials were obtained from literature, scientific articles, and research, while tertiary legal materials included legal dictionaries and news articles. Data analysis was conducted qualitatively through content analysis. The research findings indicate that the regulatory gap has led officials and the public to rely more heavily on moral or customary standards, potentially repressive, and hindered access to healthcare for groups at high risk of HIV/AIDS. Comparative studies have shown that regulations in other regions emphasize prevention rather than rights protection. This research contributes to offering a model for regional regulations that adapts to issues of morality and human rights. Therefore, balanced Regional Regulations are needed, taking local norms into account, ensuring the principle of non-discrimination, and serving as a social engineering instrument to prevent conflict, protect citizens' rights, and strengthen legal certainty in Bima Regency